Non-small Cell Lung Cancer with Multiple Brain Metastases Treated with Radiosurgery and Erlotinib: A Case Report - Sahin, Bilgehan (Cureus, 2017)
Brain metastases are commonly seen complications in non-small cell lung cancer (NSCLC) patients. The incidence of brain metastases is increasing as a result of more effective systemic targeted therapies with prolonged survival. The prognosis is usually poor, and up to six months of median survivals were reported with different therapeutic options. Here, we present an NSCLC case with multiple brain metastases treated with radiosurgery and systemic erlotinib therapy with prolonged survival. The use of tyrosine kinase inhibitors (TKI) in conjunction with either stereotactic radiosurgery or whole brain radiotherapy is not well established in terms of efficiency and toxicity. This reported case had an excellent response with a tolerable toxicity profile from the combination of either therapies.